The Historical Projections of Poverty Trapped in the Hegemony of the Capitalist Ideology within the Frame of the World Bank's Quasi-War on Poverty - Betül Sarı Aksakal (İzmir İktisat Dergisi)
The World Bank is an important international institution that plays a role in forming the perception of global poverty and the fight against poverty. Since its foundation, the Bank's approach to the concept of poverty and the policies it proposes to eliminate poverty have undergone radical changes. The study aims to reveal the theoretical and practical dimensions of the Bank's approach to poverty with their evolutionary reflections. In the study, different definitions of the World Bank regarding the concept of poverty will be included in the axis of poverty concept and different depictions of the transformation of poverty-related policies over the years. The development approach the Bank has developed for the last 40 years is likely connected to the neoliberal policies loyal to mainstream (neoclassical) economics principles. Therefore, the emphasis on the problem of poverty put by the Bank for the last few decades consists of representing the same political prescriptions to the world economies to solve the problem. In this context, it can be argued that the policies created by the Bank regarding poverty rely on ideological concerns rather than reality since it is clear that the development discourses effectuated by the Bank over the years and the policies for the elimination of poverty generated accordingly cannot be evaluated independently of the dynamics arising from the efforts of the US to perpetuate its hegemony over the international capitalist system.